Comparison of different failure criteria in prediction of safe mud weigh window in drilling practice - Maleki, S.; Gholami, Raoof; Rasouli, Vamegh; Moradzadeh, A.; Ghavami Riabi, R.; Sadaghzadeh, F. (Elsevier, 2014)
Wellbore stability is one of the most significant problems observed during drilling practice. Determination of safe mud weigh window is hence critically important in order to avoid instability problems. Mechanical properties of formations along with magnitude and direction of ins-situ stress are necessary parameters for evaluating the possibility. However, important role of an efficient failure criterion should never be neglected. In this paper three failure criteria known as Mohr-Coulomb, Hoek-Brown and Mogi-Coulomb were used for prediction of safe mud weigh window. Mechanical earth models were built using wireline logs and to get a rational conclusion, three wellbores drilled in sandstone, carbonate and gas shale reservoirs were taken into consideration. The results of this study indicated that Mohr-Coulomb criterion underestimate the strength and estimates the highest minimum mud pressure required to stabilize the wellbore. This is due to the fact that this criterion is linear and neglects the effect of intermediate stress. The Hoek–Brown criterion on the other hand due to having a non-linear equation is able to provide better estimation compared to that of the Mohr-Coulomb. However Mogi-Coulomb criterion is the best failure criterion for determination of safe mud weight window and this is due mainly to considering the effect of intermediate stress.